2012
DOI: 10.1017/s1041610212001664
|View full text |Cite
|
Sign up to set email alerts
|

Communication skills training in dementia care: a systematic review of effectiveness, training content, and didactic methods in different care settings

Abstract: This review shows that communication skills training in dementia care significantly improves the quality of life and wellbeing of people with dementia and increases positive interactions in various care settings. Communication skills training shows significant impact on professional and family caregivers' communication skills, competencies, and knowledge. Additional organizational features improve the sustainability of communication interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
266
0
7

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 259 publications
(293 citation statements)
references
References 42 publications
13
266
0
7
Order By: Relevance
“…Qualitative research indicates that acquisition of knowledge and skills can help facilitate resilience and maintaining a relationship with those cared for (Donnellan, Bennett, & Soulsby, 2015). These factors can be supported by communication and interaction based training interventions, which can enhance perceived coping and control (Eggenberger et al, 2013). However, the availability of evidence-based support and training for carers-especially family carers-is still limited (Dawson, Bowes, Kelly, Velzke, & Ward, 2015;Eggenberger et al, 2013).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Qualitative research indicates that acquisition of knowledge and skills can help facilitate resilience and maintaining a relationship with those cared for (Donnellan, Bennett, & Soulsby, 2015). These factors can be supported by communication and interaction based training interventions, which can enhance perceived coping and control (Eggenberger et al, 2013). However, the availability of evidence-based support and training for carers-especially family carers-is still limited (Dawson, Bowes, Kelly, Velzke, & Ward, 2015;Eggenberger et al, 2013).…”
mentioning
confidence: 99%
“…These factors can be supported by communication and interaction based training interventions, which can enhance perceived coping and control (Eggenberger et al, 2013). However, the availability of evidence-based support and training for carers-especially family carers-is still limited (Dawson, Bowes, Kelly, Velzke, & Ward, 2015;Eggenberger et al, 2013).…”
mentioning
confidence: 99%
“…A review of 12 trials of interventions to enhance communication in dementia care in various care settings 43 concluded that communication skills training in dementia care can improve quality of life and well-being of people with dementia and increase the quality of interactions between staff and people with dementia. The reviewers suggested that organisational features, such as incentives and 'booster' sessions for participants, might improve the sustainability of positive effects from communication interventions.…”
Section: Interventions To Improve Relational Carementioning
confidence: 99%
“…To understand these needs, an effective communication -verbal and nonverbal -is necessary 14,22 . Moreover, it is particularly important for staff working with patients with dementia to train and be educated in communication approaches 23 . Several clinical trials have been designed to improve not only the training but also the quality of life of caregivers, what leads to a better attention to the patients with dementia.…”
Section: How Difficult It Is To Evaluate Discomfort Symptoms In Patiementioning
confidence: 99%